The Effects of Weight Training Using the Normal Pyramid, Inverted Pyramid, and Double Pyramid Methods on the Lower-Body Power of Soccer Players - Muhammad Maulana Sandi; Mona Fiametta Febrianty; Geraldi Novian (Universitas Hamzanwadi, 2026)
Modern soccer demands peak physical condition, particularly lower-body power to generate explosive jumps. Although crucial, the use of pyramid-style weight training is still rare among soccer athletes. Therefore, this study aims to examine the significant effects of each method (normal, reverse, and double pyramid) on improving leg power in soccer athletes, while also identifying differences in the effects among the three methods. This quantitative study adopted a true experimental approach using a Matched-Groups Pretest-Posttest Design. Using total sampling, 30 athletes from the Asa Bina Sejahtera 19 (ABS 19) youth soccer academy were enrolled and assigned to three treatment groups using a serpentine (S-shaped) randomization pattern. Lower-body power was measured via a vertical jump test before (pretest) and after (posttest) a 4-week intervention (2 sessions/week). Data analysis employed the Paired Sample T-Test and One-Way ANOVA. The results revealed that all three pyramid methods successfully produced a statistically significant effect on leg power improvement (Sig. < 0.05). However, the One-Way ANOVA indicated no significant difference in effect among the three methods (Sig. 0.14 > 0.05). In conclusion, all three pyramid methods had an equivalent effect on increasing lower-body power. Nevertheless, descriptively, the double pyramid method recorded the highest increase.